2022
DOI: 10.1186/s12909-022-03462-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of developing scenario learning in a fundamental nursing course: a pilot study

Abstract: Background This pilot study aimed to investigate the effects of developing scenario learning (DSL) on team efficacy, systems thinking, and proactivity in problem-solving in a fundamental nursing course. Methods A total of 53 second-year nursing students were enrolled in the study; the DSL nursing education program was implemented for 15 weeks from March 4 to June 17, 2021. Data on team efficacy, systems thinking, and proactivity in problem-solving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
(24 reference statements)
1
2
0
Order By: Relevance
“…One of the limitations of this study the failure to measure all competencies and the small number of the participants, which was compensated in the present study. Baek et al (2022) reported that scenario-based learning improved team e ciency, systems thinking, and proactivity in problem-solving in nursing students without experience in nursing practicum (35). The results of this study were consistent with the data on the critical thinking dimension in the present study.…”
Section: Karageorge Et Al (2020) Assessed the Skills Of Crisis Manage...supporting
confidence: 90%
“…One of the limitations of this study the failure to measure all competencies and the small number of the participants, which was compensated in the present study. Baek et al (2022) reported that scenario-based learning improved team e ciency, systems thinking, and proactivity in problem-solving in nursing students without experience in nursing practicum (35). The results of this study were consistent with the data on the critical thinking dimension in the present study.…”
Section: Karageorge Et Al (2020) Assessed the Skills Of Crisis Manage...supporting
confidence: 90%
“…In Erenel et al, it was shown that although the scenario-based simulation method was used by educators to increase students’ preparation for practice, it led to a decrease in clinical satisfaction, decreased the students’ stress, and had no effect on the students’ self-confidence level [ 27 ]. The findings of Baek et al‘s study showed that this educational method helps to develop nursing competence in nursing students without experience in nursing internship, and the authors recommended inclusion of developing scenario learning in the nursing curriculum to promote initial adaptation to clinical environments [ 28 ]. Based on the results of these studies, it can be concluded that given the nurse anesthesia students’ dire need for preparation and effective performance of CPR, a novel and efficient teaching method should be adopted for teaching these students.…”
Section: Discussionmentioning
confidence: 99%
“…The available evidence suggests that the use of one teaching model, even a new model, is not enough to promote learning. A combination of teaching models should be used to stimulate active learning and thinking in learners [ 8 – 10 ].…”
Section: Introductionmentioning
confidence: 99%